Allelic variation in 5-HTTLPR and the effects of citalopram on the emotional neural network. (May 2015) - Ma, Yina; Li, Bingfeng; Wang, Chenbo; Zhang, Wenxia; Rao, Yi; Han, Shihui
Abstract : Background: Selective serotonin reuptake inhibitors (SSRIs), such as citalopram, which selectively block serotonin transporter (5-HTT) activity, are widely used in the treatment of depression and anxiety disorders. Numerous neuroimaging studies have examined the effects of SSRIs on emotional processes. However, there are considerable inter-individual differences in SSRI effect, and a recent meta-analysis further revealed discrepant effects of acute SSRI administration on neural responses to negative emotions in healthy adults. Aims: We examined how a variant of the serotonin-transporter polymorphism (5-HTTLPR), which affects the expression and function of 5-HTT, influenced the acute effects of an SSRI (citalopram) on emotion-related brain activity in healthy adults. Method: Combining genetic neuroimaging, pharmacological technique and a psychological paradigm of emotion recognition, we scanned the short/short (s/s) and long/long (l/l) variants of 5-HTTLPR during perception of fearful, happy and neutral facial expressions after the acute administration of an SSRI (i.e. 30mg citalopram administered orally) or placebo administration. Results: We found that 5-HTTLPR modulated the acute effects of citalopram on neural responses to negative emotions. Specifically, relative to placebo, citalopram increased amygdala and insula activity in l/l but not s/s homozygotes during perception of fearful faces. Similar analyses of brain activity in response to happy faces did not show any significant effects. Conclusions: Our combined pharmacogenetic and functional imaging results provide a neurogenetic mechanism for discrepant acute effects of SSRIs.